The Important Role of Iron, Protein and Vitamin C With the Incident of Anemia - Dilantika, Charisma; Sitorus, Nova; Saebah, Nur (Journal of Indonesian Specialized Nutrition, 2024)
Anemia is a condition where there is a lack of healthy red blood cells. Anemia can be caused by various factors, including deficiencies of iron and vitamin C. The aim of this research is to explore the important role of iron and vitamin C in preventing and treating anemia. This research adopts a qualitative approach in its research methodology. The data collection technique used is literature study. After the data is collected, analysis is carried out in three stages, namely data reduction to identify important information, data presentation to organize relevant information, and conclusion drawing to summarize the findings and their implications. The results showed that iron, protein and vitamin C have important roles in the prevention and treatment of anemia. There is a close relationship between these three components in preventing and treating anemia. Iron deficiency is the root cause of anemia, while vitamin C and protein play a role in increasing iron absorption, thus playing an important role in preventing or treating anemia. Iron is an indispensable mineral for the body to form hemoglobin and myoglobin, which are major components in the transport of oxygen and carbon dioxide. Vitamin C as an antioxidan has a positive effect on immune function and also helps the body absorb iron more easily. So to reduce the risk of anemia, by fulfilling daily protein and then eating foods rich in vitamin C and combining them with iron sources.